2018
DOI: 10.1002/prca.201800181
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Calcyclin and Heat Shock Protein 90 in Sera from Women with and without Preeclampsia by Mass Spectrometry

Abstract: Purpose The objective of present study is to determine serum levels and placental distribution of two interacting proteins calcyclin and heat shock protein 90 in preeclampsia. Experimental design Maternal serum levels of calcyclin and heat shock protein 90 are compared throughout pregnancy from the first trimester till term among women with preeclampsia (n = 43) and age‐matched normotensive pregnant controls (n = 46). A serum‐based 2D LC‐MS assay using Parallel Reaction Monitoring is applied to quantify both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…There are few and controversial reports about HSPC levels in pre‐eclampsia. Some authors have reported a strong increase of HSPC1 in serum samples from women with pre‐eclampsia in the third‐trimester of pregnancy using mass spectrometry 17 . On the other hand, decreased HSPC mRNA serum levels were found in women with pre‐eclampsia at delivery 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few and controversial reports about HSPC levels in pre‐eclampsia. Some authors have reported a strong increase of HSPC1 in serum samples from women with pre‐eclampsia in the third‐trimester of pregnancy using mass spectrometry 17 . On the other hand, decreased HSPC mRNA serum levels were found in women with pre‐eclampsia at delivery 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Hromadnikova et al 16 reported the upregulation of HSPC1 mRNA in placental tissue and the downregulation in peripheral blood of patients with pre‐eclampsia. On the other hand, Güzel et al 17 have shown that maternal serum levels of HSPC1 were significantly higher in patients with pre‐eclampsia in the third trimester of gestation compared with normotensive pregnant control women, suggesting that HSPC1 may play a role in the pathogenesis of the disease 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant expression of S100A6 was observed also in placenta of women diagnosed with preeclampsia, and its expression is increased in oxidative stress response. [ 17 ]. S100A6 was much higher in Ssc patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Calcyclin (S100A6) and Galectin 13 (PP13) are both calcium-binding proteins that have been mentioned before to be involved in PE. 28 , 29 Calcium and magnesium are administered to PE women. The literature shows that the administration of calcium might have some beneficial effect, but is not a remedy.…”
Section: Discussionmentioning
confidence: 99%